Exploring Different Aspects of Data Mining for Business (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2019)
Data Mining, also commonly known as Knowledge Discovery in Databases (KDD), mentions to the indirectly mining of implied, earlier unknown and possiblyvaluable information from data in databases.In this paper we focused on two important problems, the first students of information technology collages have greater capability in their specialist but its un clear, the second the trend in this time is using the electronic achieve but is generate huge data resulted form daily work which is difficult to control on it.in this paper we using data mining techniques rule based classification to classify the student of information technology to classes according to scientific capabilities and using Attribute Oriented Induction(AOI) data mining techniques  to solve problem of the electronic achieve. Experimental results show that the proposed techniques enhancement the method of student classification and reduce the problem that resulted from using electronic achieve., that would help improve customer experiences and decision-making.